Development of Audit Instruments and Maturity Assessment of Academic Information Systems Using COBIT 2019 (A Case Study at XYZ University) - Putri Amaliyah; Renny Sari Dewi; Rindu Puspita Wibawa; Ainur Rofik (Universitas Negeri Surabaya, 2025)
This study aims to evaluate the performance of the Digital Academic Information System (SISD) at XYZ University using the COBIT 2019 framework. The evaluation focuses on two core academic features—Study Plan Card (KRS) and Study Result Card (KHS)—to develop a systematic audit working paper and provide improvement recommendations. A qualitative case study approach was employed, with data collected through semi-structured interviews involving SISD administrators. The analysis was conducted descriptively based on the Deliver, Service, and Support (DSS) domain of COBIT 2019. The findings indicate that SISD has achieved Capability Level 3 (Defined), with an average score of 3.15. This study contributes a practical audit instrument and a capability improvement plan to strengthen information system governance in the higher education environment. In addition, the study offers a cost estimation to support comprehensive implementation planning.